MOTIVASI PENDERITA HIPERTENSI DALAM MELAKUKAN DIIT HIPERTENSI - Mujito, Mujito; Abiddin, Andi Hayyun (Fakultas Ilmu Kesehatan, Universitas Borneo Tarakan, 2023)
Hypertension diet is a way of controlling hypertension naturally and without serious side effects. This requires a high level of motivation to achieve it. This study aims to identify the client's motivation in doing a hypertension diet. The method used is an exploratory descriptive design that describes the motivation of hypertensive clients in doing a hypertension diet. The population in this study were hypertensive clients who were recorded at the InHealth InHealth Outpatient Clinic, SAM GG Kediri. The sampling technique used is quota sampling with a sample size of 30 respondents. The results showed that 76.6% of clients who did hypertension diet had high intrinsic motivation, 73.3% had high extrinsic motivation, 76.6% had high urgency motivation, 100% had high economic, social and cultural-related motivation. The motivation of hypertensive clients to have a high majority diet includes intrinsic, extrinsic, urgency and motivation related to economics, social and culture. Health care institutions are expected to continue to monitor the dietary behavior of hypertensive clients so as not to cause serious side effects.